Memori Episodik sebagai Terra Incognita yang Membatasi Neuroteknologi - Ramadhanty, Siti Azri Ulmi; Albertus, Harsawibawa (Ridwan Institute, 2021)
One of the implications of the development of neuroscience is neurotechnology. Initially, neurotechnology aims to address brain dysfunction, such as overcoming Alzheimer's disorders that cause memory loss. However, neurotechnology seems to go a step further, i.e. it not only serves to repair brain damage, but also to correct mental phenomena connected to the brain or that are